2017
DOI: 10.21470/1678-9741-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treatment Strategy of Chronic Ischemic Mitral Regurgitation on Long-Term Outcomes in Coronary Artery Bypass Grafting

Abstract: ObjectiveTo investigate the mid- and long-term outcomes of case-based selective strategy of mitral ring annuloplasty during coronary artery bypass grafting in patients with coronary artery disease accompanied by chronic ischemic mitral regurgitation.Methods132 patients who were diagnosed ischemic moderate to severe mitral regurgitation undergoing coronary artery bypass grafting in the same center with the same surgical team were divided into 2 groups and investigated retrospectively. Patients undergoing simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There are 1466 documents were initially retrieved, remove the irrelevant research, review and repetitive literature by reading the article title and abstract. Finally, 4 randomized controlled studies and 15 retrospective controlled studies were included in the study from 2001 to 2018 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . A total of 4476 patients were enrolled in this study, including 2778 patients in CABG group and 1698 patients in CMVs group.…”
Section: Results and Basic Information Of Literature Retrievalmentioning
confidence: 99%
See 2 more Smart Citations
“…There are 1466 documents were initially retrieved, remove the irrelevant research, review and repetitive literature by reading the article title and abstract. Finally, 4 randomized controlled studies and 15 retrospective controlled studies were included in the study from 2001 to 2018 [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . A total of 4476 patients were enrolled in this study, including 2778 patients in CABG group and 1698 patients in CMVs group.…”
Section: Results and Basic Information Of Literature Retrievalmentioning
confidence: 99%
“…The 16 studies [4][5][6][7][8][9][10][11][12][13][15][16][17][18]20 reported perioperative mortality after surgery, and the results showed statistical heterogeneity (p = 0.06, I 2 = 38%), so the random effect model was used for meta-analysis. The results showed that there was no significant difference in perioperative mortality between CABG group and CMVs Group (odds ratio [OR] = 0.88, 95% confident interval [CI] [0.54, 1.44], p = 0.62) (Fig.…”
Section: Perioperative Mortalitymentioning
confidence: 99%
See 1 more Smart Citation